2013
DOI: 10.3766/jaaa.24.7.10
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Underlying Individual Differences in Speech Recognition on PRESTO: A First Report

Abstract: Background Previous studies investigating speech recognition in adverse listening conditions have found extensive variability among individual listeners. However, little is currently known about the core, underlying factors that influence speech recognition abilities. Purpose To investigate sensory, perceptual, and neurocognitive differences between good and poor listeners on PRESTO, a new high-variability sentence recognition test under adverse listening conditions. Research Design Participants who fell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 87 publications
10
75
1
1
Order By: Relevance
“…With regard to inhibitory control, prior research did not find significant correlation between Stroop test and recognition performance in masking conditions ranging from primarily IM to primarily EM, including 2-talker babble (Desjardins & Doherty, 2013), 6-talker babble (Desjardins & Doherty, 2013; Tamati, et al, 2013), and SSN (Desjardins & Doherty, 2013). The current study replicated these findings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…With regard to inhibitory control, prior research did not find significant correlation between Stroop test and recognition performance in masking conditions ranging from primarily IM to primarily EM, including 2-talker babble (Desjardins & Doherty, 2013), 6-talker babble (Desjardins & Doherty, 2013; Tamati, et al, 2013), and SSN (Desjardins & Doherty, 2013). The current study replicated these findings.…”
Section: Discussionmentioning
confidence: 94%
“…Most existing studies using digit span task only investigated noise situations that primarily involved EM, such as 6-talker babble (Gordon-Salant, Yeni-Komshian, Fitzgibbons, Cohen, & Waldroup, 2013; Tamati, Gilbert, & Pisoni, 2013) and SSN (Gordon-Salant, et al, 2013; Humes et al, 1994; Kronenberger et al, 2013). Most of these studies did not find a link between digit span task (including backward and forward) and recognition performance, although one recent study from Tamati et al (2013) showed that these two span tasks were associated with recognition performance in 6-talker babble conditions when using a high-variability sentence recognition test (Gilbert, et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Speech stimuli from the Perceptually Robust English Sentence Test Open-set (PRESTO) speech corpus Tamati et al, 2013) were used. This corpus contains sentences sampled from the TIMIT database (Garofolo et al, 1993), specifically selected to create lists of sentences that are highly variable in terms of linguistic and indexical properties of the speech, but balanced for keyword frequency and familiarity.…”
Section: Introductionmentioning
confidence: 99%
“…The first was a high-variability sentence recognition task (Task 3), where every sentence was produced by a different talker. Success at such a task requires more robust perceptual representations and adaptive recognition skills than at a single-talker task (Gilbert, Tamati, & Pisoni, 2013; Tamati, Gilbert, & Pisoni, 2013). If the challenges of interactive training resulted in improvements to indexical perception, therefore, subjects in the Interactive group would do better on this high-variability task than their Lab or Control counterparts.…”
Section: Methodsmentioning
confidence: 99%